Death proof [videorecording (DVD)] - Tarantino, Quentin; Russell, Kurt; Dawson, Rosario; Ferlito, Vanessa; McGowan, Rose, 1973- (Weinstein Co. ; Genius Products, 2007)
A deranged stuntman stalks his victims from the safety of his killer car, but when he picks on the wrong group of babes, all bets are off. He becomes involved in an automotive duel of epic proportions.